Cetuximab, gemcitabine and radiotherapy in locally advanced pancreatic cancer: long-term results of the randomized controlled phase II PARC trial - Liermann, Jakob; Munter, Marc; Naumann, Patrick; Abdollahi, Amir; Krempien, Robert; Debus, Jürgen (Clinical and translational radiation oncology, 2022)
Purpose - Addressing the epidermal growth factor receptor (EGFR)-pathway by the competitive receptor ligand cetuximab is a promising strategy in pancreatic cancer. In the prospective randomized controlled phase II PARC-study (PARC: Pancreatic cancer treatment with radiotherapy (RT) and cetuximab), we evaluated safety and efficacy of a trimodal treatment scheme consisting of cetuximab, gemcitabine and RT in locally advanced pancreatic cancer (LAPC). - Methods - Between January 2005 and April 2007, 68 patients with inoperable pancreatic ductal adenocarcinoma were randomized in either trimodal therapy followed by gemcitabine maintenance (Arm A) or in trimodal therapy followed by gemcitabine plus cetuximab maintenance (Arm B). Intensity-modulated RT (IMRT) was performed with a total dose of 45 Gy in 25 fractions and with a simultaneous integrated boost to the gross tumor (54 Gy). Within the trimodal therapy, gemcitabine and cetuximab were administered weekly. Maintenance therapy consisted of gemcitabine only or gemcitabine plus cetuximab. Toxicity, overall survival (OS), secondary resection rate, local control and progression free survival (PFS) were evaluated. - Results - With a median followup time of 13 months (range: 2 - 184 months), one patient is still alive and one patient is lost to follow-up. Nausea and gastrointestinal hemorrhage were the most important higher-graded (>°II) acute and late non-hematological toxicity (13% and 7%). Median OS was 13.1 months without significant difference between both treatment arms (Arm A: 11.9 months; Arm B: 14.2 months). Compared to historical data, cetuximab did not improve OS. One- and two-year local control rates were 76.6% and 68.9%. Local tumor control and secondary resection rate (Arm A: 4%; Arm B: 16%) were significantly improved in Arm B. Median PFS was 6.8 months with distant metastasis as main treatment failure. - Conclusion - Trimodal therapy consisting of IMRT, gemcitabine and cetuximab can be considered safe and feasible. Compared to historical data, cetuximab does not improve treatment efficacy in LAPC patients treated with chemoradiation.